2017
DOI: 10.14716/ijtech.v8i7.692
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Solar Cells with TiO2 Nanoparticles Sensitized using Natural Dye Extracted from Mangosteen Pericarps

Abstract: With the increasingly shrinking reserves of fossil-based energy, as well as the damaging effects of the use of fossil-based energy sources such as the greenhouse effect and global warming, efforts are needed to find energy alternatives. One device being developed as an alternative source of renewable energy by utilizing solar energy source is dye-sensitized solar cells (DSSC) that works using simple photosynthetic-electrochemical principle in the molecular level. In this device, the inorganic oxide semiconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…In terms of the sensitizing dye, the finding agrees with other results in which the PCE of the DSSC device sensitized using the dye extracted using ethanol containing 20% distilled water is higher than that of pure ethanol. The current PCE is also higher than the PCE obtained by Singh et al Although the difference is yet to be further confirmed, it is expected that the difference in the process during the extraction could result in the difference in the obtained dye.…”
Section: Resultssupporting
confidence: 90%
“…In terms of the sensitizing dye, the finding agrees with other results in which the PCE of the DSSC device sensitized using the dye extracted using ethanol containing 20% distilled water is higher than that of pure ethanol. The current PCE is also higher than the PCE obtained by Singh et al Although the difference is yet to be further confirmed, it is expected that the difference in the process during the extraction could result in the difference in the obtained dye.…”
Section: Resultssupporting
confidence: 90%
“…Details of the data are presented in Table 3. As a comparison, the results of a DSSC device using platinum paste as a counter electrode (Sofyan et al, 2017) are also presented in this table.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, nano-sized titanium dioxide (TiO2) has been widely considered as one of the most photoactive materials for catalysis in various photocatalytic reactions, due to its chemical stability, low toxicity and corrosion resistance (Low et al, 2017). Studies have shown that multiple forms of TiO2 nanostructures have been extensively used as photocatalytic material in photo-induced solar fuel generation, such as CO2 reduction and water splitting, photo oxidation of pollutants in wastewater remediation, and photovoltaic devices (Ayati et al, 2014;Clavero, 2014;Tahir & Amin, 2015;Sofyan et al, 2017). Unfortunately, the large TiO2 bandgap (~3.2 eV) often limits its application in the development of solar-driven photocatalytic reactions, as it only absorbs in the ultraviolet (UV) region (Dette et al, 2014).…”
Section: Introductionmentioning
confidence: 99%